2013
DOI: 10.1016/j.radmeas.2013.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation properties of pure and Ce3+-doped SrF2 crystals

Abstract: In this paper results of scintillation properties measurements of pure and Ce 3+ -doped strontium fluoride crystals are presented. We measure light output, scintillation decay time profile and temperature stability of light output. X-ray excited luminescence outputs corrected for spectral response of monochromator and photomultiplier for pure SrF 2 and SrF 2 -0.3 mol.% Ce 3+ are approximately 95% and 115% of NaI-Tl emission output, respectively. A photopeak with a 10% full width at half maximum is observed at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 17 publications
1
25
0
4
Order By: Relevance
“…(20,21) In addition to the excellent scintillation characteristics, these perovskite chloride host crystals require no special handling or packaging techniques because they are less hygroscopic than commercial halide scintillators such as NaI:Tl and (24,25) to our best knowledge, no other study on crystal growth, photoluminescence, and scintillation properties of the CsSrCl 3 :Ce has been reported so far. In this paper, we report the photoluminescence and scintillation characterizations of the CsSrCl 3 :Ce crystal grown by the vertical Bridgman method.…”
Section: +mentioning
confidence: 99%
“…(20,21) In addition to the excellent scintillation characteristics, these perovskite chloride host crystals require no special handling or packaging techniques because they are less hygroscopic than commercial halide scintillators such as NaI:Tl and (24,25) to our best knowledge, no other study on crystal growth, photoluminescence, and scintillation properties of the CsSrCl 3 :Ce has been reported so far. In this paper, we report the photoluminescence and scintillation characterizations of the CsSrCl 3 :Ce crystal grown by the vertical Bridgman method.…”
Section: +mentioning
confidence: 99%
“…Their structural, optical, lattice dymamic and elastic properties have been extensively studied [1][2][3][4][5][6]. Due to their unique properties, including low energy phonons, optical transparency, high resistivity and anionic conductivity [7], SrF 2 has been applied in scintillation detectors [8] and luminiscent materials [9,10]. As other members of the MF 2 , SrF 2 undergoes a series of pressure induced phase transitions to highly coordinated [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been considered as a good phosphor host material that can be doped by a number of lanthanide ions for various luminescent applications [1,2,3,4]. SrF 2 host material doped with Ce 3+ lanthanide ions is an example of a phosphor material that is extensively being investigated specifically for light amplification [5,6]. Some of these light amplification studies proposed that the SrF 2 :Ce 3+ phosphor material could be a promising scintillator [5].…”
Section: Introductionmentioning
confidence: 99%
“…SrF 2 host material doped with Ce 3+ lanthanide ions is an example of a phosphor material that is extensively being investigated specifically for light amplification [5,6]. Some of these light amplification studies proposed that the SrF 2 :Ce 3+ phosphor material could be a promising scintillator [5]. Shendrik et al [5] reported efficient scintillation light output of SrF 2 :Ce 3+ with high temperature stability suggesting that this material can be applied in well-logging scintillation detectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation